Analysis Of Factors That Influence Customer Satisfaction In Grab Indonesia - Syafiqah Dewi Ramadhani; Fathin Alia Hamdi; Dr. Osly Usman, M.Bus Syst (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Customer Experience, Service Quality, and Promotion on customer satisfaction through consumer trust among Grab Indonesia users. This research uses a quantitative approach with primary data collection through online questionnaires. Respondents were selected using purposive sampling, with a total of 105 respondents, 100 of whom used Grab Indonesia, while 5 did not. The entire population was used as the research sample. Data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the aid of Smart PLS 4.0.9.3 software. The statistical analysis includes descriptive analysis, convergent and discriminant validity tests, reliability tests (Cronbach’s alpha and composite reliability), variable relationship tests, and hypothesis testing. The results show that Customer Experience positively and significantly affects customer satisfaction through consumer trust in Grab Indonesia. Service Quality also has a significant positive effect, while Promotion does not significantly influence customer satisfaction through consumer trust in Grab Indonesia. It can be concluded that improving customer experience and service quality is crucial to enhancing customer satisfaction in Grab Indonesia. However, there is no significant evidence that increased purchasing decisions will lead to higher customer loyalty.